SERVANT LEADERSHIP DALAM IMPLEMENTASI NILAI-NILAI TRILOGI DAN PANCA KESADARAN SANTRI - Saifur Rizal (STAI Ma'had Aly Al-Hikam Malang, 2019)
The number of theories and models of leadership is a positive response from experts and scientists of various countries as a form of attention to the development and demands of the times. Likewise in the world of education, many leadership theories require educational institutions to be able to make changes in the framework of developing education towards progress in achieving a goal. Servant leadership is one of them, this leadership concept was taught and applied by Prophet Muhammad 14 centuries ago and was reiterated by Greenleaf several years ago. Servant leadership of a leadership theory that is widely applied in the world of Islamic education, especially Islamic boarding schools as the oldest Islamic educational institution in Indonesia. Including Nurul Jadid Islamic Boarding School in implementing trilogy values and the five santri awareness that are carried out continuously. In the process of implementing trilogy values and awareness of all santri in various management activities it is the main role in running a system. Servant leadership is a milestone in the success of the planting of these values to be able to be imbued by every santri to plunge into society.